Task type, preference, and occupation affect standing desk utilization in office workers. - DiRocco, Tara; Hall-Nelson, Brianna; Carlson, Ingrid; Corrigan, John; Kutcher, Stephanie; Mertz, Patrick; Nelson-Wong, Erika (Work, 2023)
BACKGROUND: Adjustable height sit-stand desks are becoming the norm in many workplaces. It is not known how task type, worker preference, and occupation impact utilization of the adjustable height feature. OBJECTIVE: This survey-based study aimed to determine how task type, preference and occupation affect office workers' sitting and standing behaviors at work. METHODS: Office workers (n = 123) from different occupations completed surveys about actual and preferred positions (sit, stand, either/both) during 39 common tasks from 4 different categories, as well as barriers to use. Each position was analyzed by task type, behavior, and occupation. RESULTS: There were differences between actual and preferred behavior for each position, with participants sitting more and standing less than preferred across all task categories. There were differences between task categories with participants sitting less for generative and routine, and standing more for communication tasks. The highest rates of either/both responses were for routine tasks. Engineers reported the lowest standing rates, and also indicated standing more than preferred. Information Tech and Engineering had the highest either/both responses. Finance reported the highest sitting rates. Personal, task-based and workplace limitations were cited as barriers to preferred use. CONCLUSION: Office workers would prefer to stand more at work. Occupation-specific needs and preferences, as well as types of tasks should be considered when providing workplace standing options.